Colonial discourse: postcolonial theory - Barker, Francis (Viva books, 2012)
Recently, the issues of colonialism and imperialism have, for the first time, come to the forefront of thinking in the humanities. This volume examines relevant issues from a range of historical perspectives. Central to the whole volume is a critique of the idea of the "post-colonial" itself.